2014
DOI: 10.1007/s10900-014-9872-4
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Delay in Seeking Malaria Treatment for Children Under-Five Years in Parts of South Eastern Nigeria

Abstract: One of the components of the current WHO strategy to fight malaria is early recognition and prompt and appropriate treatment. We investigated determinants of delay in seeking early and appropriate malaria treatment for children (0-5 years) in Ohaji/Egbema, South Eastern Nigeria. Data was collected using structured pre-tested questionnaires elicited in the local language (Igbo) to 738 consenting mothers within the child bearing age (15-49 years). About twenty-two percent (22%) of the respondents sought treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
46
3
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 24 publications
9
46
3
3
Order By: Relevance
“…The prevalence observed in our study is comparable to that of 87.8% reported by Dida et al (2015) in Ethiopia [18]. On the other hand, some results obtained in other African countries have shown the average prevalence of delay in health care utilization, as in Uganda (55.2%), Tanzania (55.4%), and Nigeria (51.5%) [19][20][21]. These results show that the delay in the provision of malaria treatment to health facilities is high in the communities of sub-Saharan Africa.…”
Section: Prevalence Of Delays In Hcumt In Childrensupporting
confidence: 86%
See 2 more Smart Citations
“…The prevalence observed in our study is comparable to that of 87.8% reported by Dida et al (2015) in Ethiopia [18]. On the other hand, some results obtained in other African countries have shown the average prevalence of delay in health care utilization, as in Uganda (55.2%), Tanzania (55.4%), and Nigeria (51.5%) [19][20][21]. These results show that the delay in the provision of malaria treatment to health facilities is high in the communities of sub-Saharan Africa.…”
Section: Prevalence Of Delays In Hcumt In Childrensupporting
confidence: 86%
“…The practice of home care is very common, as in Senegal, where the results of a survey revealed that 91.1% of children suffering from malaria receive self-medication before resorting to an external source. As confirmed by our findings, a multi-center study in six countries in sub-Saharan Africa, including Benin, revealed the multiple sources of malaria treatment among children under five [17][18][19][20][21][22][23]. 4…”
Section: Therapeutic Itinerarysupporting
confidence: 79%
See 1 more Smart Citation
“…12,13 Demographic, socioeconomic, and behavioral factors and distance from residence to health facilities are known determinants of delayed seeking of appropriate care among children with malaria. [14][15][16][17][18][19][20] However, their contribution to severe malaria is unclear, with available studies yielding conflicting results. 6,12,13,[21][22][23][24][25] Variations in findings may be attributable to differences in study design and analysis, varied impacts of complex host-parasite interactions that affect disease presentation and small sample sizes.…”
Section: Introductionmentioning
confidence: 99%
“…Evidences showed that most malaria-related deaths in malariaaffected countries occur at home without receiving appropriate medical care, and when care is sought, it was often delayed [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%